Laundry butler by Tidytools / Muhammad Danish Haikal Azman … [et al.] - Azman, Muhammad Danish Haikal; Mohd Aspar, Daniel Hani; Hairulazhar, Nafiz Akmal; Che Zalman, Muhammad Zaquan Hakimi; Azis, Siti Noraziana; Naseri, Roszi Naszariah Nasni (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
This abstract introduces a novel laundry basket designed to improve accessibility and independence for individuals with disabilities especially people who suffered from spinal cord injuries. The product addresses the challenges often faced during laundry tasks, such as bending, lifting, and carrying heavy loads. We detail the innovative features of the basket, focusing on ergonomic design principles that promote ease of use. These may include elements like elevated base for reduced bending strain, lightweight yet durable materials for effortless lifting and built-in handles and straps for comfortable carrying. The abstract concludes by highlighting the potential benefits of this laundry basket design. These include increased independence, reduced physical strain, and improved overall laundry experience for people with disabilities.